In situ adaptive tabulation (ISAT) for combustion chemistry in a network of perfectly stirred reactors (PSRs). (2nd February 2017) - Adhikari, Sudip; Sayre, Alan; Chandy, Abhilash J.
Abstract : Graphical abstract: Abstract : Highlights: An efficient computational implementation of ISAT in a network of PSRs is presented. A series of PSR calculations is carried out using the DI and ISAT approaches. Validation of DI is performed through comparisons with previous experiments. ISAT is assessed through direct comparisons with DI calculations. Analysis of accessed composition space, sensitivity and speedup is conducted. Abstract: This paper presents an efficient computational implementation of the in situ adaptive tabulation (ISAT) approach (Pope, 1997 ) for combustion chemistry in a network of perfectly stirred reactors (PSRs). A series of PSR calculations is carried out using the direct integration (DI) and ISAT approaches, and validation of DI is performed through comparisons with previous experiments. Assessment of the accuracy of ISAT approach is conducted through direct comparisons with DI calculations. Moreover, accessed region of the composition space, sensitivity of ISAT calculations with respect to the absolute error tolerance values and speedup are analyzed for two different test cases, a hydrogen–air and an ethylene–air combustion case. In summary, the hydrogen–air case resulted in a speedup of 9.8 for 1 million of PSRs in series, whereas for the ethylene–air case it was 42 for 0.3 million PSRs.